Analisis Nilai Tambah Pengolahan Abon Ikan Tuna di Kelurahan Mata Kecamatan Kendari Kota Kendari - Dzulmawan, Muhammad; Geo, Laode; Gafaruddin, Abdul (Department of Agribusiness, Halu Oleo University, 2018)
This study aims to: Know the factors that affect farmers in patchouli farming in the Village The purpose of this research is to analyze the amount of profit and value added that resulted in the processing of tuna fish abon in household industry